2018
DOI: 10.11118/actaun201866020357
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc and Copper on Anaerobic Stabilization of Sewage Sludge

Abstract: The most frequently found metals in municipal sewage sludge are copper and zinc. The aim of this study was to the evaluate effect of these metals on anaerobic microorganisms during sewage sludge stabilization. Anaerobic fermentation tests were carried out in 24 batch fermenters with hydraulic retention time 21 days at mesophilic temperature conditions 38 °C ± 0.2 °C. Five different concentrations of metal ionts (100-1000 mg•l -1 ) were tested. Cumulative biogas and methane production were used as the comparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…We found that the hydrogen concentration was greater than 16790 ppm during the biogas analysis, indicating that the hydrogenotrophic methanogenic -Archea was inhibited. So we concluded that ≈ 50% of biogas is produced by acetate as which was reported in the literature [44,46]. Also, this is consistent with the study performed by Li and Fang (2007), who evaluated the toxic effect of HMs on Hydrogen-producing bacteria (HPB), and they concluded that the HPB showed a higher resistance to HMs toxicity than methanogenic bacteria.…”
Section: Effect Of Hms On Cod Removalsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that the hydrogen concentration was greater than 16790 ppm during the biogas analysis, indicating that the hydrogenotrophic methanogenic -Archea was inhibited. So we concluded that ≈ 50% of biogas is produced by acetate as which was reported in the literature [44,46]. Also, this is consistent with the study performed by Li and Fang (2007), who evaluated the toxic effect of HMs on Hydrogen-producing bacteria (HPB), and they concluded that the HPB showed a higher resistance to HMs toxicity than methanogenic bacteria.…”
Section: Effect Of Hms On Cod Removalsupporting
confidence: 90%
“…According to [41], the relative toxicity of HMs is Pb < Zn ≈ Ni < Cu, as determined by the inhibition of methane formation and the methanogenic activity analysis, and Pb < Ni < Cr < Cu < Cd, as determined by Lin (1993) [42] and Chen et al ( 2008) [43].According to another study implemented by Dokulilová et al (2018), the lowest concentration of zinc Zn+2 and Cu+2 which causes the high inhibition of biogas yield is 400 mg/l Zn+2 and 1000 mg/l Cu+2, [42]. Mudhoo and Kumar (2013) reported that the toxic order of the high concentrations of HM was Pb < Ni < Cd < Cu < Cr < Zn [45].…”
Section: Effect Of Hms On Cod Removalmentioning
confidence: 99%
“…Zinc represents the largest elemental concentration in sludge, and mainly enters the wastewater system in run‐off from gutters, roofing and galvanized surfaces, and from the use of detergents and washing powders, and body care products containing Zn (Dokulilová et al, 2018). However, the decline in non‐ferrous metal manufacture, and Zn smelting in particular, which ended in the United Kingdom in 2003, has reduced Zn and associated Cd emissions to the environment and their concentrations in sludge.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to maintain process stability, it is crucial to keep the balance between the acid and methane forming microorganisms to optimising methane generation from the AD process. Previous studies also demonstrated that the presence of inhibitory substances in substantial concentrations (such as sodium chloride (Zhao et al 2017), ammonia (Siles et al 2010), sulphate (Siles et al 2010), hydrogen sulphide (Hilton and Archer 1988), heavy metals (Dokulilova et al 2018), and some organic compounds (Chen et al 2008)) often cause failure in AD process. The inhibitors causing adverse shifts in microbial community composition and/or inhibit bacterial growth that influences AD performance.…”
Section: Effect Of Process Parameters and Inhibitory Substances On MImentioning
confidence: 99%